Leukocyte Membrane Enzymes Play the Cell Adhesion Game - López-Cortés, Georgina I.; Díaz-Alvarez, Laura; Ortega, Enrique (Frontiers in Immunology, 2021)
For a long time, proteins with enzymatic activity have not been usually considered to carry out other functions different from catalyzing chemical reactions within or outside the cell. Nevertheless, in the last few years several reports have uncovered the participation of numerous enzymes in other processes, placing them in the category of moonlighting proteins. Some moonlighting enzymes have been shown to participate in complex processes such as cell adhesion. Cell adhesion plays a physiological role in multiple processes: it enables cells to establish close contact with one another, allowing communication; it is a key step during cell migration; it is also involved in tightly binding neighboring cells in tissues, etc. Importantly, cell adhesion is also of great importance in pathophysiological scenarios like migration and metastasis establishment of cancer cells. Cell adhesion is strictly regulated through numerous switches: proteins, glycoproteins and other components of the cell membrane. Recently, several cell membrane enzymes have been reported to participate in distinct steps of the cell adhesion process. Here, we review a variety of examples of membrane bound enzymes participating in adhesion of immune cells.